(untitled) (Bangladesh Journal of Zoology, 2010)
Investigations were made on the changes of quality of salted hilsa (Tenualosa ilisha) and also to evaluate the effect of irradiation for their preservation at low temperature (0-4ºC). Prior to storage, total viable bacterial count (TVBC), total psychrophilic bacterial count (TSBC) and total fungal count (TFC) were 2.8×106, 9.52×104 and 8.12×104 cfu/g, respectively. TVBC, TSBC and TFC were found to decrease gradually after six months of storage. TVBC and TSBC decreased after treatment with gamma radiation doses at 2.5 and 5.0 kGy, respectively and no count was found when treated with gamma radiation dose at 7.5 kGy. Total fungi were completely eliminated at 5.0 and 7.5 kGy. Counts of total viable bacteria and psychrophilic bacteria of all the fish samples decreased to below 104 /g at 5.0 kGy of irradiation. During storage period at low temperature (0-4ºC) the residual bacteria decreased more rapidly in irradiated samples than in non-irradiated samples. Different physico-chemical parameters regarded as the indices of spoilage were studied from the non-irradiated and irradiated fish samples during storage period. Moisture content, protein content were found to decrease, while tyrosine values (TV) were found to increase, during storage compared to non-irradiated samples. The initial values of all the indices were less in irradiated samples except protein content and the increasing or decreasing rate was also affected by the radiation during storage period. Bangladesh J. Zool. 38(1): 13-22, 2010